Correlation and Path Coefficient Analysis for Yield and its Phenological, Physiological, Morphological and Biochemical Traits under 60 mM Salinity Stress in Chickpea (Cicer arietinum L.) - Tutlani, Aman; Jaiswal, Priyanka; Kumar, Rajneesh; Rashid, Munezeh; Hussan, Shamshir UL; Bashir, Iram; Chouhan, Shambhu; Kumari, Smita; Dar, Zahoor A.; Lone, Ajaz A.; et al. (International Journal of Bio-resource and Stress Management, 2024)
The investigation was carried out during rabi season (November–April) of 2020–2021 in the polyhouse, Department of Genetics and Plant Breeding, Lovely Professional University, Phagwara, Punjab, India to assess the performance of chickpea genotypes under salinity stress conditions. The experiment was conducted using a Completely Randomized Design (CRD) with three replications under two conditions: saline (pots without holes) and control (pots with holes). Twenty genotypes were collected out of which seventeen from ICRISAT, Hyderabad and three from ARS, SriGanganagar. The salinity stress was created using salts NaCl, which were administered in split doses of 60 mM at the time of sowing and 15 DAS. The study monitored various parameters such as phenological, physiological, morphological, biochemical, and yield parameters to determine the effect of salt stress on genotypes exhibiting different tolerance levels. The results showed that the total proline content increased due to the production of stress-related proteins during salinity stress. However, the yield parameters were reduced under stress conditions, with the highest decrease observed in the 60 mM NaCl treatment group compared to the control group. Based on the results of the study, ICC5439 and GNG 1581 are highly tolerant chickpea genotypes under salinity stress conditions. ICC 6050, ICC 251, ICC 252, and ICC 262 are medium tolerant genotypes, while ICC253, ICC 247, and ICC 249 are highly susceptible genotypes. Remaining are minimum tolerant and sensitive genotypes.